Bitcoin, LQ45, Gold, and Rupiah Exchange Rate: A Comparative Study for Investment Decisions - Fandi Ahmad; Purwanto Purwanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to compare the performance of four investment instruments: the cryptocurrency Bitcoin, LQ45 stocks, gold, and the rupiah exchange rate against the dollar in determining investment decisions. The growing public interest in various forms of investment, particularly digital assets like Bitcoin, has emphasized the importance of analysis that considers risk and return. This study employed a quantitative method with a comparative approach. The data used were the annual closing prices of each investment instrument for the period 2014 to 2023. Performance analysis was conducted using three evaluation methods: the Sharpe, Treynor, and Jensen methods. The results show significant differences in performance between investment instruments depending on the measurement method used. Bitcoin exhibits high returns but also carries high risk, while gold demonstrates greater stability, and LQ45 stocks have experienced a post-pandemic recovery. The rupiah exchange rate against the dollar is influenced by external factors such as monetary policy and global economic conditions. This study contributes to investors' selection of investment instruments that align with their risk profiles and serves as a reference for financial institutions and academics in understanding the characteristics of each instrument.